Competitive effects of wild Radish Raphanus raphanistrum.L on The growth and yield of wheat Triticum Durum. In Jabal Akhdaar (Libya) - Hesean, Taib. Farag (Al-Mukhtar Journal of Sciences, 2002)
The wild radish weed was commonly distributed in most wheat crop fields within Al-Gabal Al-Akhdaar Libya and responsible for reduced the crop yield by 8.35%. For this reason this study was performed in the East area of Al-Jabal Al-Akhdar at Elgobaa governorate by using additive technique of competitive determination using constant number of wild radish seedling at the rates of 242 and 482 as medium and high, density respectively compared with pure farming. Results showed that the competitive coefficient was significant either within species or between the two species at different growth stages under medium and high competitive rates. The loss of yield capacity calculated by the coefficient of damage (q) was significantly increased with increasing levels of weed competition at all growth stages compared with pure farming. The (q) values were 0.46 kg2 and 3.84 kg-2 after one and four months from planting time at medium competitive rate, while at high rate the q values were 1.8 kg-2 and 5.4 kg2 after same period from planting, respectively. Moreover, the competitive by wild radish reflected on decreasing the grain yield from 4.63 t-1 to 1.62 t-1 and straw yield from 20.98 t-1 to 5.62 t-1 respectively. Finally the competition by wild radish weed in wheat crop fields were signiticantive orqualitative characteristics of wheat by 42.33, 27% and 51% for grains yield, straw yield and seed index, respectively as compares by pure farming.